IMPACT OF SELECTED AGRICULTURAL EXTENSION PROGRAMMES ON VULNERABILITY TO POVERTY AMONG RURAL FARMING HOUSEHOLDS IN SOUTHWEST, NIGERIA - Alawiye, M. A.; Adeyemi, T. O.A.; Yusuf, A. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examines the impact of selected agricultural extension programmes on vulnerability to poverty among rural farming households in Southwest Nigeria. Using cross-sectional primary data from 673 farm households collected between 2025 and 2026 in Oyo and Osun States, the study applies probit regression to model the probability of extension programme participation and employs Propensity Score Matching (PSM) to estimate causal impacts. The result shows Vulnerability as Expected Poverty (VEP) framework identifies 36.4 percent of households as vulnerable, with 225 households simultaneously poor and vulnerable. Socio-economic characteristics significantly correlated with vulnerability include age, farm size, farming experience, household size, and credit access. Agricultural extension participation, particularly through farmer empowerment and new agricultural technology programmes, significantly attenuates vulnerability. The study advocates for disaggregated, vulnerability-targeted extension policies that prioritise currently non-poor but at-risk households, alongside broader structural reforms addressing credit access, infrastructure, and gender inclusion in agricultural advisory services.